2020
DOI: 10.1155/2020/3436549
|View full text |Cite
|
Sign up to set email alerts
|

Association between Circulating B-Type Natriuretic Peptide and Diabetic Peripheral Neuropathy: A Cross-Sectional Study of a Chinese Type 2 Diabetic Population

Abstract: Cardiovascular disease which is associated with cardiac dysfunction, usually measured with circulating levels of B-type natriuretic peptide (BNP), has been associated with incidence and progression of diabetic peripheral neuropathy (DPN). The potential relationship of circulating physiological levels of BNP with DPN, however, has not been reported. Circulating levels of BNP were measured in 258 patients with type 2 diabetes mellitus (T2DM), and participants were divided into a DPN group ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Body mass index (BMI) was calculated by dividing weight in kilograms by height in metres squared. Systolic and diastolic blood pressures were measured in all subjects on the right arm using a standard mercury sphygmomanometer [18]. All measurements were operated by trained study personnel.…”
Section: Clinical and Biochemical Measurementsmentioning
confidence: 99%
“…Body mass index (BMI) was calculated by dividing weight in kilograms by height in metres squared. Systolic and diastolic blood pressures were measured in all subjects on the right arm using a standard mercury sphygmomanometer [18]. All measurements were operated by trained study personnel.…”
Section: Clinical and Biochemical Measurementsmentioning
confidence: 99%
“…Diabetic peripheral neuropathy (DPN) is one of the common complications of diabetes. DPN is clinically characterized by peripheral nerve dysfunction accompanied with typical features of numbness and pain [1,2] . The study has shown that in 2017 there are 451 million diabetic patients worldwide, and it was expected to increase up to 693 million by 2045 [3] .…”
Section: Introductionmentioning
confidence: 99%
“…DPN is clinically characterized by peripheral nerve dysfunction accompanied with typical features of numbness and pain. [1,2] The study has shown that in 2017 there are 451 million diabetic patients worldwide, and it was expected to increase up to 693 million by 2045. [3] Global incidence of DPN among diabetic patients is 9.6 -88.7 % and continues to increase.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 60 studies were included in the systematic review,26–85 with 43 of those studies including at least one arterial stiffness measurement suitable for meta-analysis 29–31 33–35 37–39 41 42 46 47 52 53 55 57 59–77 79–85. Although various studies adjusted for age, sex, diabetes duration, or SBP in data analysis, the values used in the meta-analyses were not adjusted for, other than those studies that only included participants of one sex 65 75.…”
Section: Resultsmentioning
confidence: 99%
“…For the purposes of investigating arterial stiffness and neuropathy, we classified 53 of the studies as cross-sectional,26 28–31 33–36 38–62 64–67 69 71 73–85 5 as case-control37 63 68 70 72 and 2 as cohort 27 32. For cross-sectional studies, all participants had diabetes, except Allison et al 26 and Kuo et al ,46 who included participants regardless of diabetes status, as well as Cho et al ,35 who alongside participants with diabetes, also separately analyzed those with no history of disease known to cause PN.…”
Section: Resultsmentioning
confidence: 99%